Identity and Difference in Aelius Aristides' "Regarding Sarapis". Issue 2 (4th May 2019) - Atwill, Janet M.; Portz, Josie
ABSTRACT: This article posits that bringing diversity to histories of rhetoric may require not only revising canons but also "unwriting" the narratives of Western civilization in which canonical figures have been cast. Two conventions of these narratives are of special significance: fixed identities and narrative coherence. Focusing on the cultural contexts of Aelius Aristides' "Regarding Sarapis, " we suggest that these conventions obscure the cultural differences that were always there.